RELIGIOUS VALUE IN THE SHORT STORY “PEREMPUAN YANG MENARI BERSAMA OMBAK” BY RINAL SAHPUTRA - Harfiandi; Mayang Sari (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
This research examines religious values as a reflection of the character of the actor who experiences an event in the story. The aim of this research is to reveal the religious values in the short story